Eksplorasi kemampuan penalaran visual siswa pada materi perbandingan trigonometri ditintau dari gender - Prasetyo, Muhammad Ponco; Buchori, Achmad (Mahesa Research Center, 2024)
The aim of this research is to analyze the visual reasoning abilities of high school students based on gender using trigonometry comparison material. The subject consists of two students with the provisions of one male student and one female student. Data was collected by administering a visual reasoning test to 10 10th grade students, then the selected subjects were interviewed. The data validation used is the triangulation method. Data analysis techniques use data reduction, data presentation and conclusion drawing. The results of the research showed that male students in the trigonometry comparison material were able to identify side sides, slanted sides, front sides, and were able to determine the use of the cos and tan formulas to solve problems with correct calculations. Meanwhile, female students in the trigonometry comparison material were able to identify side sides, slanted sides, front sides, were able to determine the use of the cos and tan formulas, but were less precise in determining the value of cos 30°, and less precise in making the final decision because they did not convert it into units. the same thing, namely meters.